2018
DOI: 10.1093/nar/gky535
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional regulation of Pabpn1 by the RNA binding protein HuR

Abstract: RNA processing is critical for proper spatial and temporal control of gene expression. The ubiquitous nuclear polyadenosine RNA binding protein, PABPN1, post-transcriptionally regulates multiple steps of gene expression. Mutations in the PABPN1 gene expanding an N-terminal alanine tract in the PABPN1 protein from 10 alanines to 11–18 alanines cause the muscle-specific disease oculopharyngeal muscular dystrophy (OPMD), which affects eyelid, pharynx, and proximal limb muscles. Previous work revealed that the Pab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…Consistent with previous observations 26 , we were unsuccessful in immunoprecipitating HuR from skeletal muscle extracts. Therefore, we used the well-established C2C12 myoblasts, to assess, as we did before 9,11,12,27 , the association between HuR and PGC-1α mRNA. Similar to what was observed in the soleus , small- interfering ribonucleic acid (siRNA)-mediated HuR depletion in C2C12 myoblasts 11,12 significantly increased PGC-1α mRNA and protein levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with previous observations 26 , we were unsuccessful in immunoprecipitating HuR from skeletal muscle extracts. Therefore, we used the well-established C2C12 myoblasts, to assess, as we did before 9,11,12,27 , the association between HuR and PGC-1α mRNA. Similar to what was observed in the soleus , small- interfering ribonucleic acid (siRNA)-mediated HuR depletion in C2C12 myoblasts 11,12 significantly increased PGC-1α mRNA and protein levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, recent studies suggest that the pathogenic mechanism of OPMD is related to sequestration of PABPN1, other proteins, and RNAs in nuclear aggregates, thus decreasing the functional pools of these important molecules (7,13,14). Given that PABPN1 protein levels in muscle are already low (15), sequestration into aggregates or interaction with alanine-expanded PABPN1 may decrease available PABPN1 below some threshold required for normal muscle function (15,16). If alanine expansion also impairs normal PABPN1 function, this could compound any defects associated with decreased PABPN1 availability and exacerbate pathology.…”
mentioning
confidence: 99%
“…Further analyses showed that the human antigen R (HuR) protein interacts with ARE4 and represses Pabpn1 expression in mature muscle. [91] The two isoforms of Pabpn1 also trigger PABPN1 autoregulation. The distal PAS creates an unspliced pre-mRNA that includes intron 6.…”
Section: The Regulation Of Pabpnsmentioning
confidence: 99%
“…Further analyses showed that the human antigen R (HuR) protein interacts with ARE4 and represses Pabpn1 expression in mature muscle. [ 91 ]…”
Section: Nuclear Poly(a) Binding Proteinsmentioning
confidence: 99%